Penggunaan Dual-Layer Substrate untuk Meningkatkan Bandwidth Antena Mikrostrip pada Frekuensi LTE - Rudy Fernandez; Febrian Akbar Pratama (JURNAL NASIONAL TEKNIK ELEKTRO, 2018)
Narrow bandwidth is one of the problems in a microstrip antenna. Bandwidth enhancement is proposed by applying dual-layer in the substrate. The bottom layer is made from a single-layer circular microstrip antenna design by applying the formula to get an initial dimension and then it is simulated by an EM Simulator to verify its performance whether meet the specific requirement. The dimension of optimized design is used as a dimension for the top layer but without the ground plane. The antenna uses substrate FR4 which has thickness of 1.6 mm with dielectric constant of 4.3. The simulation result of the dual-layer antenna in frequency band 40 LTE shows that there is an additional bandwidth of 46% with return loss -23.45 dB, antenna gain 0.34 dB and directional radiation pattern. Keywords : Microstrip Antenna, Return Loss and Dual-layer